2020
DOI: 10.1111/pce.13948
|View full text |Cite
|
Sign up to set email alerts
|

Light acts as a stressor and influences abiotic and biotic stress responses in plants

Abstract: Light is important for plants as an energy source and a developmental signal, but it can also cause stress to plants and modulates responses to stress. Excess and fluctuating light result in photoinhibition and reactive oxygen species (ROS) accumulation around photosystems II and I, respectively. Ultraviolet light causes photodamage to DNA and a prolongation of the light period initiates the photoperiod stress syndrome. Changes in light quality and quantity, as well as in light duration are also key factors im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 224 publications
3
104
0
1
Order By: Relevance
“…How the different pathways, networks, and hormones that regulate each of the plant responses to stress interact with each other, and how these interactions are regulated during a stress combination, are mostly open questions that await further research. There are many examples of signal transduction and hormone interactions in plants, including the integration of light and heat, or light and pathogen, signaling via different light receptors (e.g., [64]), the antagonistic functions of different plant hormones such as JA and SA (e.g., [45]), or the impact of epigenetic control over the activation of particular stress-response pathways (e.g., [65,66]). The identification of unique transcriptional regulators (transcription factors, TFs) and quantitative trait loci (QTLs) associated with stress combinations should begin to uncover some answers (e.g., [38][39][40]44,[47][48][49][50][51][52]).…”
Section: The Impact Of Multifactorial Stress Combinations On Plant Mementioning
confidence: 99%
“…How the different pathways, networks, and hormones that regulate each of the plant responses to stress interact with each other, and how these interactions are regulated during a stress combination, are mostly open questions that await further research. There are many examples of signal transduction and hormone interactions in plants, including the integration of light and heat, or light and pathogen, signaling via different light receptors (e.g., [64]), the antagonistic functions of different plant hormones such as JA and SA (e.g., [45]), or the impact of epigenetic control over the activation of particular stress-response pathways (e.g., [65,66]). The identification of unique transcriptional regulators (transcription factors, TFs) and quantitative trait loci (QTLs) associated with stress combinations should begin to uncover some answers (e.g., [38][39][40]44,[47][48][49][50][51][52]).…”
Section: The Impact Of Multifactorial Stress Combinations On Plant Mementioning
confidence: 99%
“…The ability of plants to sense and react to different adverse conditions in their environment by modulating physiological responses, gene expression and metabolism, is crucial for plant adaptation and survival during stress. Due to the frequent occurrence of HL+HS combination in nature, and its impact on crops (Yamamoto et al, 2008;Suzuki et al, 2014;Roeber et al, 2020), as well as its impact on plant survival (Balfagón et al, 2019), the study of metabolic changes during this stress combination is of particular interest. A recent study of the physiological and transcriptomic responses of Arabidopsis plants subjected to HL, HS and their combination (HL+HS) revealed that the HL+HS combination was accompanied by irreversible damage to PSII, decreased D1 (PsbA) protein levels, enhanced accumulation of the hormones jasmonic acid (JA) and JA-isoleucine (JA-Ile), elevated expression of over 2,200 different transcripts unique to the stress combination, distinctive structural changes to chloroplasts and a decreased survival rate (Balfagón et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Plants growing under natural conditions are exposed to different abiotic and biotic stresses that impact plant growth and development. Among these, high light intensities that exceed the plant photosynthetic capacity often occur in native habitats (Ort, 2001;Roeber et al, 2020). Because light plays a key role in the life of photosynthetic organisms, plants evolved many different acclimation and adaptation mechanisms to counteract the effect of high light stress, including paraheliotropic movements, pathways for adjusting the size of the antenna complexes, quenching mechanisms, and pathways to scavenge excess reactive oxygen species (ROS;Asada, 2006;Li et al, 2009;Dietz, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light is crucial for the activation of full resistance responses in plant-pathogen interactions, for both the induction of local defense responses as well as for the transcriptional regulation required for SAR (for review: Ballaré (2014); Roeber, Bajaj, Rohde, Schmulling, and Cortleven (2020)). Several studies have shown that in particular the length of the light period determines the strength of the plant immune response in Arabidopssi thaliana (Cecchini et al, 2002;Griebel & Zeier, 2008).…”
Section: Introductionmentioning
confidence: 99%